Bone regeneration at the distal aspect of the adjacent second molar after lower third molar coronectomy: a long-term analysis - Leung, Yiu Yan; Yeung, Andy Wai Kan; Ismail, Izzati Nabilah Ismail; Wong, Natalie Sui Miu (Churchill Livingstone, 2020)
Abstract. A residual bone defect at the distal aspect of the adjacent second molar may occur after total removal of the lower third molar. Lower third molar coronectomy has been proved to be a safe alternative to total removal, but the extent of bone regeneration at the adjacent tooth after coronectomy is not well reported. The aim of this prospective study was to investigate the long-term bone regeneration at the distal aspect of the adjacent second molar after lower third molar coronectomy. Preoperative and postoperative cone beam computed tomography scans were measured to assess bone regeneration at the distobuccal (DB), mid-distal (MD), and distolingual (DL) aspects of the lower second molar. Forty-eight coronectomies in 37 patients (23 female) with a mean (standard deviation) age of 29.1 (7.2) years were assessed. The mean follow-up was 93.2 (8.7) months. The mean bone level increase at DB, MD, and DL aspects was 3.2 (1.6) mm, 3.5 (1.5) mm, and 3.2 (1.6) mm, respectively; the bone levels were significantly higher than the preoperative measurements (P < 0.001). Age and impaction patterns were not factors affecting bone regeneration. Based on this study, it appears that coronectomy of the lower third molar brings favourable bone regeneration at the distal aspect of the adjacent second molar.